The Relevance of the Development of Learning Tools and Media during the Time of the Prophet Muhammad in the Context of Artificial Intelligence (AI) from the Perspective of Hadith - Aris Priyanto; Muhammad Mufid; Dwi Maya Meilina; Niza Afriyah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Background of the Study: The advancement of educational technology has entered a new phase with the emergence of artificial intelligence (AI), which offers rapid information access and learning efficiency. However, its application within Islamic education requires critical examination to ensure alignment with prophetic values. Historically, educational practices during the time of Prophet Muhammad SAW utilized various forms of teaching media, ranging from exemplary behavior, gestures, questioning techniques, to the use of concrete objects to enhance comprehension. This becomes a reflective basis for assessing the role of AI in contemporary learning. Methods: This study employs a qualitative library research approach through a review of classical Islamic sources, hadiths related to the Prophet’s pedagogical methods, and recent studies concerning the implementation of AI in education. Key Findings: The study reveals that the utilization of instructional tools is not a modern concept in Islam. AI represents an evolutionary phase of media use that shares the same objective as prophetic teaching—to support understanding, interaction, and value internalization. While AI may enhance learning effectiveness and accessibility, its use requires value-based regulation to preserve moral formation and learner independence. Contribution: This research provides a historical-normative framework for integrating AI into Islamic education while maintaining prophetic principles. Conclusion: AI has the potential to become an effective learning medium as long as its implementation strengthens comprehension, character, and spiritual awareness. Further empirical research is recommended to examine its practical impact in real educational settings.